Investigation Biosorption Potential of Copper and Lead from Industrial Waste-Water Using Orange and Lemon Peels - Husoon, Z A; Al-Azzawi, M N A; Al-Hiyaly, S A K (Al-Nahrain Journal of Science, 2013)
Much attention has been made towards adsorbent materials to be used in heavy metal removal from polluted water and various techniques are applied such as chemical, physical and biological techniques. This study was designed for using less expensive and much frequently available materials (orange & lemon peels) to remove copper and lead from industrial waste-water. Three forms of these peels (fresh dried small pieces and powder) were used. Also other factors such as pH and temperature were examined for probable effects on biosorption. Current data show that both orange and lemon peels are capable of removing copper and lead ions at significant capacity. Furthermore, lemon peels had higher capability than orange peels and the form of peel powder of both orange and lemon showed higher capacity than fresh and dried pieces where lemon powder has shown biosorption capacity of 72.5% and 71.3% for lead and copper respectively while orange powder had bioremoval percentage of 56.7% of lead and 34.5% for copper. In case of fresh lemon peels, these figures were 70.9% for lead and 62.2% for copper but fresh orange peels gave much less percentage (48.7of lead and 29.6% of copper). Regarding dried peels which showed the lowest values, but again, lemon peels were significantly better than those of orange. These values of lemon were 58.0% for lead and 57.1% for copper but for orange peels, the biosorption percentages reached 37.2% and 23.7% for lead and copper respectively. However, biosorption capacity of both fruit peels at different forms were significantly affected by various levels of both pH and temperature. The optimum pH and temperature values for better bioremoval capacity for all treatment within this study were 5 and 40 C° for pH and temperature respectively. Based on above, current data found that lemon peels are more efficient than the orange peels as biosorbents materials.